Transition metal nanomaterial-based electrocatalysts for water and CO2 electrolysis: preparation, catalytic activity, and prospects - Maduraiveeran, Govindhan (Frontiers in Energy Research, 2024)
The production of hydrogen (H2) and multi-carbon fuels through water electrolysis (oxygen evolution reaction (OER)/hydrogen evolution reaction (HER)) and water–CO2 co-electrolysis (OER/CO2 reduction reaction (CO2RR)), respectively, is supposed to be the emergent energy carrier. These electrochemical processes are essential chemical conversion pathways that initiate the changes toward production of renewable energy. This review summarizes the systematic design of earth-abundant transition metal-based nanomaterials and their electrocatalytic activities toward electrochemical energy conversion reactions such as OER, HER, and CO2RR. The primary focus is on fabricating highly effective, low-cost, and advanced transition metal-based nanostructures for both the OER/HER and OER/CO2RR systems. Developing synthetic strategies for surface morphology-controlled nanostructured electrocatalysts, engineering the electrode surface, enhancing the electrocatalytic activity, understanding the relationship between intrinsic catalytic activity and preparation approaches or precursor choices, and exploring the reaction mechanism are focused on. Furthermore, the current challenges, figure-of-merit, and prospects of transition metal-based nanomaterials and their electrocatalytic activities toward water electrolysis and water–CO2 co-electrolysis are described. This study may open new opportunities to develop shape-controlled and high-performance electrocatalysts for electrochemical energy conversion and storage reactions.